Química orgânica: proposta de ensino com base no modelo de equivalência de estímulos - César, Marcelo de Abreu (2014)
The Behavior Analysis has developed studies based on stimulus equivalence model for understanding diverse academic repertoires. Whereas in Brazil, teaching chemistry remains a major challenge, this study evaluated a program for teaching organic chemistry, which is based on stimulus equivalence model and implemented in the collective space, with the aid of a software. Participating students were in the 2nd year of high school. Two experiments, both with Pre-Test - Intervention and Post Test, were performed . In Experiment 1, it was taught to verbalize chemical elements based on their symbolic representations, numbers and atomic models. The stimuli were: printed name (A), symbol (B), atomic number (C) and atomic model (E) of chemical elements. The AB, BC and BE relations were taught, and tested to BA, CB, AC, CA, EB, AE, EA, CE, EC, and naming the chemical element from the symbol (BD), atomic number (CD) and atomic model (ED). In Experiment 2, it was taught to verbalize different types of carbon chains formulas, to identify the different formulations of the same carbon chain and also to classify the carbon chains as to whether or not the existence of free extremities related to existing connections between the carbon atoms and the presence or not of the heteroatom. Stimuli stated the type of formula (I) the type of formula representation (II), printed name of the type of formula (III), flat structural formula (A), formula line (B), condensed structural formula (C), molecular formula (D), printed name of the extremity (E1), printed name of the connection type (E2), printed name referring to the existence of atom (E3). It began by teaching the relation I-II, and by testing relations II-III, III-II and also the verbalization of the type of formula (II-O). In the sequence, the AB and AC relations were taught, and the BC, CB, BA and CA relations were tested; the AD relation, testing DA, BD, DB, CD, DC; the CE1 relation, testing E1C, AE1, E1A, BE1, E1B, DE1, E1D; compared to CE2, testing E2C, AE2, E2A, BE2, E2B, DE2, E2D, the CE3 relations, testing E3C, AE3, E3A, BE3, E3B, DE3, E3D. Generalization test was conducted for the New Carbonic Chains. The results indicated that participating students reached the expected level of performance in all the taught and tested relationships and that, new repertoires arose from these relations, including verbalization and construction (design) of the type of formula. Performance in the Post-Test was higher than in the Pre-Test, and there was widespread repertoire, demonstrating the effectiveness of the evaluated program for the organic chemistry teaching